So Much Wasted : Hunger, Performance, and the Morbidity of Resistance - Anderson, Patrick, 1974- (Book collections on Project MUSE., 2010)
A performance project on self-starvation in the clinic, the arts, and prison, which considers starvation as a gendered practice.